2017
DOI: 10.1186/s12879-016-2171-1
|View full text |Cite
|
Sign up to set email alerts
|

High rates of multidrug-resistant and rifampicin-resistant tuberculosis among re-treatment cases: where do they come from?

Abstract: BackgroundGlobally 3.9% of new and 21% of re-treatment tuberculosis (TB) cases are multidrug-resistant or rifampicin-resistant (MDR/RR), which is often interpreted as evidence that drug resistance results mainly from poor treatment adherence. This study aims to assess the respective contributions of the different causal pathways leading to MDR/RR-TB at re-treatment.MethodsWe use a simple mathematical model to simulate progression between the different stages of disease and treatment for patients diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 27 publications
3
37
0
5
Order By: Relevance
“…Acquired MDR‐TB, the most common type of MDR‐TB in many settings, occurs as a result of sub‐optimal first‐line TB treatment, which is often related to health system or patient factors (Faustini, Hall, & Perucci, ; Han et al, ). There is increasing evidence that primary MDR‐TB is common and that many patients with MDR‐TB had it from the start of treatment, highlighting the need for universal drug susceptibility testing (Dheda et al (); Ragonnet, Trauer, Denholm, Marais, & McBryde, ; Shah et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Acquired MDR‐TB, the most common type of MDR‐TB in many settings, occurs as a result of sub‐optimal first‐line TB treatment, which is often related to health system or patient factors (Faustini, Hall, & Perucci, ; Han et al, ). There is increasing evidence that primary MDR‐TB is common and that many patients with MDR‐TB had it from the start of treatment, highlighting the need for universal drug susceptibility testing (Dheda et al (); Ragonnet, Trauer, Denholm, Marais, & McBryde, ; Shah et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…5 However, it has been demonstrated that many retreatment cases with MDR-TB also represent transmitted drug resistance. 6 The epidemic spread of MDR-TB is a particular concern in areas with poor control of ongoing TB transmission, especially among HIV-infected patients with severe immunodeficiency where health-care facilities can serve as epidemic amplifiers. 7,8 Global TB control efforts have been complicated by increased drug resistance and the negative synergism of TB and HIV coinfection.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a high incidence of new cases of TB worldwide because of the increased population, the oating population, the increased incidence of drug-resistant TB, latent infection, and the AIDS epidemic. 28,29 In 2015, the WHO proposed a moratorium on TB that aimed to reduce the incidence of TB by 90% by 2035. 30 At present, there is no early diagnostic procedure for TB, leading to delayed treatment in most TB patients.…”
Section: Discussionmentioning
confidence: 99%